2019
DOI: 10.1111/acer.14184
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Alcohol Consumption and Risk of Nasopharyngeal Carcinoma: A Comprehensive Meta‐Analysis of Epidemiological Studies

Abstract: Background: Alcohol consumption is increasing all over the world, but whether it is an independent factor affecting the occurrence of nasopharyngeal carcinoma (NPC) is inconsistent in many studies. We aimed to explore the association between alcohol consumption and NPC risk by integrating existing evidence in a meta-analysis.Methods: We searched for relevant articles published up to August 2018 in PubMed, Cochrane Library, Web of Science, and China National Knowledge infrastructure (CNKI). The Newcastle-Ottawa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…The reported association between alcohol intake and NPC risk is inconsistent, with statistically null results in several studies, especially in high-incidence areas, but positive associations in other studies in high-and low-incidence populations (105,106). Two meta-analyses found a positive meta-RR for the highest versus the lowest category of alcohol intake in combined case-control studies, with a J-shaped exposure-response curve that, if real, may contribute to the inconsistency of results across study populations with different alcohol drinking habits (105,106). The lack of association between alcohol and NPC risk in two prospective cohort studies in Singapore (107) and Shanghai (108), however, suggests that bias may contribute to the positive findings in case-control studies.…”
Section: Alcohol and Teamentioning
confidence: 99%
“…The reported association between alcohol intake and NPC risk is inconsistent, with statistically null results in several studies, especially in high-incidence areas, but positive associations in other studies in high-and low-incidence populations (105,106). Two meta-analyses found a positive meta-RR for the highest versus the lowest category of alcohol intake in combined case-control studies, with a J-shaped exposure-response curve that, if real, may contribute to the inconsistency of results across study populations with different alcohol drinking habits (105,106). The lack of association between alcohol and NPC risk in two prospective cohort studies in Singapore (107) and Shanghai (108), however, suggests that bias may contribute to the positive findings in case-control studies.…”
Section: Alcohol and Teamentioning
confidence: 99%
“…Another case-control report, which included 240 cancer cases, has observed a linear relationship between drinking frequency and overall upper aerodigestive tract cancers (p for trend = 0.01) [14], whereas no association was observed between oral cancer subtype (n = 187) and drinking frequency in a study based on the same data [15]. There are few meta-analyses or systematic reviews on drinking frequency and overall HNC risk, but one meta-analysis of cohort studies has examined the association between nasopharyngeal cancer risk and drinking frequency [16]. Frequent drinking (≥7 times per week) was related to an increase in the risk of nasopharyngeal cancer (pooled odds ratio [OR] 1.29, 95% CI 1.05-1.53) in this analysis, whereas infrequent drinking (<7 times per week) showed the contrasting result (pooled OR 0.77, 95% CI 0.60-0.94).…”
Section: Introductionmentioning
confidence: 99%
“…Other research has reported that heavy alcohol consumption can increase the risk of certain cancer types, including HNC cancers and NPC [11]. In studies involving East Asian populations, the presence of genetic polymorphisms in ADH1B (rs1229984) and ALDH2 (rs671), as well as alcohol consumption, individually or in combination [13], increase the risk of breast cancer [36], HNC [17], and esophageal cancer [18,35].…”
Section: Discussionmentioning
confidence: 99%
“…The association between alcohol consumption and NPC risk is inconsistent in many studies [9,10]. Two meta-analyses have indicated that the risk of developing NPC may increase with alcohol consumption; in both meta-analyses, drinking and high-frequency drinking increased the risk of NPC [11,12].…”
Section: Introductionmentioning
confidence: 99%